Rod Rotating with a ring -part 1

A rod of length l l and mass m m hinged at one end is rotating in a horizontal plane at an angular speed of w w , initially. A ring of same mass m m is at a distance of l / 2 l/2 from the fixed end initially and has z e r o zero velocity w.r.t. rod. The system is left to itself until the ring reaches the end of the rod. Determine the velocity v 2 v^{2} of ring w.r.t inertial frame.

Details and assumptions

  • w w =2/21
  • l = 168 m l = 168 m
  • Neglect friction everywhere


The answer is 133.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mark Hennings
Mar 6, 2018

If the bead is a distance r r from the centre of rotation when the rod makes and angle θ \theta with its initial direction, then the angular momentum of the system about the centre of rotation is constant, and hence 1 3 m 2 θ ˙ + m r × r θ ˙ \tfrac13m\ell^2 \dot{\theta} + mr \times r\dot{\theta} is constant. Thus 1 3 m ( 2 + 3 r 2 ) θ ˙ = 7 12 m 2 ω θ ˙ = 7 2 ω 4 ( 2 + 3 r 2 ) \begin{aligned} \tfrac13m(\ell^2 + 3r^2)\dot{\theta} & = \; \tfrac{7}{12} m\ell^2\omega \\ \dot{\theta} & = \; \frac{7 \ell^2 \omega}{4(\ell^2 + 3r^2)} \end{aligned} Since the rod is smooth, the only force acting on the bead is transverse, and so the radial acceleration of the bead is zero. Thus r ¨ r θ ˙ 2 = 0 \ddot{r} - r\dot{\theta}^2 = 0 , and so r ¨ = r θ ˙ 2 = 49 4 ω 2 r 16 ( 2 + 3 r 2 ) 2 1 2 r ˙ 2 = 7 24 2 ω 2 49 4 ω 2 96 ( 2 + 3 r 2 ) = 7 2 ω 2 96 ( 2 + 3 r 2 ) [ 4 ( 2 + 3 r 2 ) 7 2 ] r ˙ 2 = 7 2 ω 2 ( 4 r 2 2 ) 16 ( 2 + 3 r 2 ) \begin{aligned} \ddot{r} & = \; r\dot{\theta}^2 \; = \; \frac{49 \ell^4 \omega^2 r}{16(\ell^2 + 3r^2)^2} \\ \tfrac12\dot{r}^2 & = \; \tfrac{7}{24}\ell^2\omega^2 - \frac{49\ell^4 \omega^2}{96(\ell^2 + 3r^2)} \; = \; \frac{7\ell^2 \omega^2}{96(\ell^2 + 3r^2)}\big[ 4(\ell^2 +3r^2) - 7\ell^2\big] \\ \dot{r}^2 & = \; \frac{7\ell^2 \omega^2(4r^2 - \ell^2)}{16(\ell^2 + 3r^2)} \end{aligned} Thus, when r = r =\ell , θ ˙ = 7 16 ω \dot{\theta} = \tfrac{7}{16}\omega and r ˙ 2 = 21 64 2 ω 2 \dot{r}^2 = \tfrac{21}{64}\ell^2\omega^2 , and hence v 2 = r ˙ 2 + 2 θ ˙ 2 = 21 64 2 ω 2 + 49 256 2 ω 2 = 133 256 2 ω 2 v^2 \; = \; \dot{r}^2 + \ell^2\dot{\theta}^2 \; = \; \tfrac{21}{64}\ell^2\omega^2 + \tfrac{49}{256}\ell^2\omega^2 \; = \; \tfrac{133}{256}\ell^2\omega^2 With = 168 \ell = 168 and ω = 2 21 \omega = \tfrac{2}{21} we have ω = 16 \ell \omega = 16 , and this makes v 2 = 133 v^2 = \boxed{133} .

good solution! .

rakshith lokesh - 3 years, 2 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...